Because Moms Say So: Narratives of Lesbian Mothers in Italy. Issue 1 (1st January 2016) - Zamperini, Adriano; Testoni, Ines; Primo, David; Prandelli, Marta, Chiara Monti
ABSTRACT: The Italian situation of lesbian women-parented families seems to be trapped between a deprivation of public and legal acknowledgment and the reality of everyday lives of lesbian women having children in a same-sex relationship context experiencing this ambivalence in their personal, familiar, and social existence. The aim of this study is to analyze the narratives of 17 lesbian mothers (10 biological mothers and seven social mothers) in order to outline the construction of their identities as parents, their affective relationships with the partner (social mother), and the relationships established with public agencies (school, neighborhood, family networks). Results show that lesbian maternity has strong political and social implications. In particular, our analysis underlines the libertarian extent of lesbian maternity paths, often based on equal roles and promoting the enlargement of the concepts of family. Our findings suggest that the lack of legal recognition has a threatening effect on the sense-making processes that social mothers perform during the development of their parental role.